CRISPR interference to evaluate modifiers of C9ORF72-mediated toxicity in FTD - Pickles, Sarah; Zanetti Alepuz, Desiree; Koike, Yuka; Yue, Mei; Tong, Jimei; Liu, Pinghu; Zhou, Yugui; Jansen-West, Karen; Daughrity, Lillian M.; Song, Yuping; DeTure, Michael; Oskarsson, Björn; et al. (Frontiers in Cell and Developmental Biology, 2023)
Treatments for neurodegenerative disease, including Frontotemporal dementia (FTD) and Amyotrophic lateral sclerosis (ALS), remain rather limited, underscoring the need for greater mechanistic insight and disease-relevant models. Our ability to develop novel disease models of genetic risk factors, disease modifiers, and other FTD/ALS-relevant targets is impeded by the significant amount of time and capital required to develop conventional knockout and transgenic mice. To overcome these limitations, we have generated a novel CRISPRi interference (CRISPRi) knockin mouse. CRISPRi uses a catalytically dead form of Cas9, fused to a transcriptional repressor to knockdown protein expression, following the introduction of single guide RNA against the gene of interest. To validate the utility of this model we have selected the TAR DNA binding protein (TDP-43) splicing target, stathmin-2 (STMN2). STMN2 RNA is downregulated in FTD/ALS due to loss of TDP-43 activity and STMN2 loss is suggested to play a role in ALS pathogenesis. The involvement of STMN2 loss of function in FTD has yet to be determined. We find that STMN2 protein levels in familial FTD cases are significantly reduced compared to controls, supporting that STMN2 depletion may be involved in the pathogenesis of FTD. Here, we provide proof-of-concept that we can simultaneously knock down Stmn2 and express the expanded repeat in the Chromosome 9 open reading frame 72 (C9ORF72) gene, successfully replicating features of C9-associated pathology. Of interest, depletion of Stmn2 had no effect on expression or deposition of dipeptide repeat proteins (DPRs), but significantly decreased the number of phosphorylated Tdp-43 (pTdp-43) inclusions. We submit that our novel CRISPRi mouse provides a versatile and rapid method to silence gene expression in vivo and propose this model will be useful to understand gene function in isolation or in the context of other neurodegenerative disease models.